Penyelesaian Sengketa Mawah di Lembaga Adat Aceh dalam Hukum Islam - mardhatillah, Fitria; Maghfirah, Fitri; Thani, Shira (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
Mawah transactions in Aceh is agree orally without written evidence, potentially leading to prolonged disputes. The mawah agreement does not mention a time limit for the duration of the agreement with a certain period of time, causing the heirs of the mawah property manager to sue. If there is a dispute in Acehnese society (including mawah disputes) it will be resolved through peaceful means and/or customary courts before being handed over to the police. This research approach uses an empirical juridical approach that aims to examine aspects that must be considered in resolving mawah disputes and procedures for resolving mawah disputes in Aceh Customary Institutions based on Islamic law. The results showed that aspects of the agreement, legal aspects and judges need to be observed so that the settlement does not violate Islamic law. The dispute resolution procedure in the Acehnese customary court is in accordance with the settlement in Islam which is in the nature of the settlement in accordance with peace (aṣṣulh) and the form of implementation is in accordance with the judiciary (al-qaḍā) with an appeal at the Mukim level if Keuchik unable to complete. Furthermore, if the customary court has not been able to be resolved it will be resolved through the Religious court, for Aceh the Religious court is called the Shar'iyah Court.